The Exchange Rate Effects of a Singaporean Closed-Border Retail Central Bank Digital Currency: A Counterfactual Analysis - Agrawal, Arnav (Theoretical and Practical Research in Economic Fields, 2026)
Central bank digital currencies (CBDCs) are heralded as the next innovation in currency usage. Their unique architecture provides both liquidity and remuneration to investors. This paper aims to assess the exchange rate changes caused by differing plausible implementations of CBDCs due to changes in portfolio allocations of investors. Furthermore, the paper also aims to identify the ideal form of CBDC implementation. This study uses a novel aggregated uncovered interest parity equation to connect interest rate differentials between Singaporean and international assets to estimate exchange rate differentials. Three counterfactual CBDC regimes are modelled over the period between 2000 Q1 and 2024 Q4, namely the Baseline Rule (no interest rate on CBDCs), the Markdown Rule (a discounted rate on CBDCs), and the Taylor Rule (interest rate set as per inflation and output gaps). These regimes are compared with the non-CBDC counterfactual which is modelled using the standard uncovered interest parity equation. The criteria for comparison are path fidelity and volatility of the exchange rate. It was found that the Markdown Rule is the ideal form of CBDC implementation. Furthermore, it was also found that the Singapore dollar appreciates 35.8% to 80.4% across CBDC regimes. These findings are of great importance to the Monetary Authority of Singapore, as they can significantly affect its unique exchange-rate-targeting monetary policy.